Microwave Pyrolysis of Agricultural and Plastic Wastes for Production of Hybrid Biochar: Applications for Greener Environment - Sridevi, Veluru; Hamzah, Husam Talib; Jweeg, Muhsin Jaber; Mohammed, M. N.; Al-Zahiwat, M. M.; Abdullah, Thamer Adnan; Abdullah, Oday I. (Universitas Pendidikan Indonesia, 2024)
The microwave-assisted pyrolysis (MAP) is a promising technology for converting waste feedstocks (AWB and PW) into valuable products, primarily biochar. The residual product generated from the AWB and PW MAP process is called hybrid biochar. The hybrid biochar made by MP is highly stable, has distinctive physical and chemical characteristics, and outperforms its conventional usage. Microwave heating is an efficient and fast energy heating method. It helps with yield production, eliminates the need for liquid convection, makes thermal control easier, restores waste products' chemical and energy value, and produces the highest quality and most cost-effective hybrid biochar. Different feedstocks and microwave pyrolysis settings affect how well hybrid biochar restores the environment. This article examines hybrid biochar's potential to boost agricultural productivity, nutrient availability, co-composting, water retention, and consumption efficiency. The report also reveals knowledge gaps and suggests further research to better understand hybrid biochar deployment. The study also detailed hybrid biochar's production, characterization and, most importantly, environmental use.